Cisplatin and lipopolysaccharide co-administration for renal injury model in mice - Sae-Byeok Hwang; Soon-Suk Kang; Yeonmi Lee; Eunju Kang (Journal of Animal Reproduction and Biotechnology)
Background: Cisplatin, a chemotherapeutic agent often causes nephrotoxic side effects. Lipopolysaccharide (LPS) is known to induce pro-inflammatory responses, often leading to septic renal injury. We hypothesized that the combination of cisplatin and LPS would amplify renal injury, thereby improving a renal injury model. Therefore, we administered both agents to mice and evaluated renal injury indicators. Methods: Eight-week-old male C57BL/6 mice were injected with cisplatin (8, 10, or 12 mg/kg) and LPS (5 mg/kg) on days 1 and 4 following of each week. Mice were euthanized at specific time points to assess renal injury. Body weight, renal weight, area, and BUN levels were measured to evaluate renal damage. Additionally, hematoxylin and eosin (H&E) and Masson’s trichrome (MT) staining were performed to assess histological changes. Results: The combination of cisplatin and LPS significantly reduced body and renal weight compared to cisplatin alone. A high dose of cisplatin (12 mg/kg) resulted in a 50% mortality, while, lower doses (8 and 10 mg/kg) showed 100% survival. Significant renal injury was observed in the 10 mg/kg cisplatin group administered for two weeks. In the 8 mg/kg cisplatin group, no changes were observed after two weeks, but renal damage appeared after four weeks. Histological evaluations in the 10 mg/kg cisplatin group administered for two weeks showed renal injury features, including tubular damage and fibrosis. Conclusions: Administering cisplatin (10 mg/kg) with LPS for two weeks or cisplatin (8 mg/kg) with LPS for four weeks resulted in a distinct renal injury, effectively establishing a renal injury mouse model.